2009
DOI: 10.1002/adsc.200800771
|View full text |Cite
|
Sign up to set email alerts
|

Pyrrolidine‐Camphor Derivative as an Organocatalyst for Asymmetic Michael Additions of α,α‐Disubstituted Aldehydes to β‐Nitroalkenes: Construction of Quaternary Carbon‐Bearing Aldehydes under Solvent‐Free Conditions

Abstract: A novel pyrrolidine-camphor organocatalyst 3 was designed, synthesized and proven to be an efficient catalyst for the asymmetric Michael reaction. Treatment of a,a-disubstituted aldehydes with b-nitroalkenes in the presence of 20 mol% organocatalyst 3 and 20 mol% benzoic acid under solvent-free conditions provided the desired Michael product possessing an all-carbon quaternary center with high chemical yields (up to 99% yield) and high levels of enantioselectivities (up to 95% ee).Keywords: asymmetric catalysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(14 citation statements)
references
References 88 publications
0
14
0
Order By: Relevance
“…1f,g [α] 26 D = +1.7° (c = 1.0, CHCl3), white solid, Mp. 58-59 °C, δH(CDCl3) 1.00 (3H, s), 1.13 (3H, s), 3.73 (1H, dd, J 4.2, 11.5 Hz), 3.79 (3H,s),4.66 (1H,dd,J 4.2,12.8 Hz),4.81 (1H,dd,J 11.5,12.8 Hz),6.86 (2H,d,J 8.7 Hz),7.11 (2H,d,J 8.7 Hz), 9.53 (1H, s); δC(CDCl3) 18.7, 21.4, 47.7, 48.2, 55.1, 76.4, 113.9, 126.9, 130.0, 159.2, 204.3; ν(KBr)/cm -1 2976,2919,2841,2718,1725,1611,1582,1553,1516,1468,1441,1379,1290,1250,1188,1119,1028,889,839,812,747,635 8, 21.6, 47.8, 48.0, 75.9, 122.1, 130.6, 131.8, 134.3, 203.7; ν(KBr)/cm -1 3030,2973,2934,2874,2818,2718,1728,1559,1487,1468,1441,1410,1381,1350,1306,…”
mentioning
confidence: 99%
“…1f,g [α] 26 D = +1.7° (c = 1.0, CHCl3), white solid, Mp. 58-59 °C, δH(CDCl3) 1.00 (3H, s), 1.13 (3H, s), 3.73 (1H, dd, J 4.2, 11.5 Hz), 3.79 (3H,s),4.66 (1H,dd,J 4.2,12.8 Hz),4.81 (1H,dd,J 11.5,12.8 Hz),6.86 (2H,d,J 8.7 Hz),7.11 (2H,d,J 8.7 Hz), 9.53 (1H, s); δC(CDCl3) 18.7, 21.4, 47.7, 48.2, 55.1, 76.4, 113.9, 126.9, 130.0, 159.2, 204.3; ν(KBr)/cm -1 2976,2919,2841,2718,1725,1611,1582,1553,1516,1468,1441,1379,1290,1250,1188,1119,1028,889,839,812,747,635 8, 21.6, 47.8, 48.0, 75.9, 122.1, 130.6, 131.8, 134.3, 203.7; ν(KBr)/cm -1 3030,2973,2934,2874,2818,2718,1728,1559,1487,1468,1441,1410,1381,1350,1306,…”
mentioning
confidence: 99%
“…Luo and Chan reported that diphenylperhydroindolinol silyl ether 34 [56], which was A novel prolinamide-camphor catalyst 35 has been discovered for the direct asymmetric Michael addition of aldehydes to nitroolefins in high yields and excellent diastereo-and enantioselectivities [57]. For the Michael addition of a, adisubstituted aldehydes to nitroolefins, the pyrrolidine-camphor catalyst 36 exhibited high efficiency under neat conditions [58].…”
Section: Asymmetric Michael Addition Reactionsmentioning
confidence: 98%
“…In 2009, Chen and co‐workers designed a novel pyrrolidine‐camphor organocatalyst 62 for the asymmetric Michael addition reaction . The model reaction of isobutyraldehyde with trans‐β‐nitrostyrene was explored in different solvent and amount of catalyst.…”
Section: Solvent‐free Reactions In Asymmetric Catalysismentioning
confidence: 99%